Effect of lipoic acid on spermatological and biochemical parameters following equilibration and freeze-thawing of ram semen - Nuri Başpınar; Kenan Çoyan; Mustafa Numan Bucak; Ali Doğan Ömür; Mehmet Bozkurt Ataman; Pınar Peker Akalın; Şükrü Güngör; Caner Öztürk (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the effects of different doses of lipoic acid added into dilution extender, following equilibration and freeze-thawing of ram semen on spermatologic and biochemical parameters. Materials and Methods: The ejaculates collected from 6 mature Konya Merino rams were used in the research. Ejaculates containing approximately 400x106 spermatozoa were diluted at 37 ºC with the Tris-based extender containing lipoic acid at the doses of 1, 2, 4 mM and no additive (control), and then, they were frozen. Results: After equilibration, all doses of lipoic acid did not affect the sperm parameters whereas lipoic acid 1 mM (74.3%) ameliorated motility compared to both control (62.5%) and lipoic acid 4 mM (65.0%) (p<0.001) groups after freeze-thawing. Lipoic acid did not affect HOS test and acrosome integrity of spermatozoa following freeze-thaw-ing. Also, the supplementation of lipoic acid at 1, 2 and 4 mM doses did not provide any significant effect on the levels ofbiochemical parameters (p>0.05). Conclusion: Addition of 1 mM lipoic acid to ram semen increases the motility after freeze-thawing process. However, dose treatments of lipoic acid in different extenders and animal species-breeds are required to be performed.